Pedobarographic Measurements of Rheumatoid Feet Compared with Clinical Parameters - Yasemin YUMUSAKHUYLU; Bilinc DOGRUOZ KARATEKIN; Selin TURAN TURGUT; Afitap ICAGASIOGLU; Esra SELIMOGLU; Sadiye MURAT; Esen KASAPOGLU; Bekir TURGUT (Medeniyet Medical Journal)
Objective: This study aimed to investigate the relationship between plantar pressure pedobarographic measurements and disease activity, radiological abnormali-ties, and foot indexes in patients with rheumatoid arthritis (RA). Methods: Sociodemographics, foot symptoms, anatomical distribution, pain intensity and duration, and podiatry services access data were collected. Disease activity scale of 28 joints (DAS28) was used for the disease activity, and Health Assessment Questionnaire (HAQ) was used for the functional status. Foot function index (FFI) was used to measure the impact of foot pathology on its function. The Modified Larsen scoring was used to assess radiological abnormalities. Pedobarog-raphic measurements were used to analyze foot loading characteristics. Results: A total of 104 feet of 52 patients with RA was evaluated. DAS28 scores did not correlate with the plantar pressure values (p>0.05). A significant correlation was found between HAQ scores and right medial midfoot loading pressure (r=0.355; p<0.01). FFI scores were positively correlated with right lateral midfoot loading pressure (r=0.302; p<0.05). No relationship was found between Manchester Foot Pain and Disability Index and plantar loading characteristics. The radiological scores were correlated with left lateral hindfoot plantar pressure (r=0.286; p<0.05). Conclusions: Pedobarographic measurements can be considered as a follow-up evaluation tool for the evaluation of all foot parts (forefoot, midfoot, and hindfoot). Rheumatoid feet investigation showed that foot involvement is independent of the disease duration, whereas midfoot plantar pressures are associated with the body mass index. Additionally, DAS28 may fall short as a marker of disease activity because it neglects foot problems.